1996
DOI: 10.1007/bf00130411
|View full text |Cite
|
Sign up to set email alerts
|

Agent heterogeneity and consensual decision making on the Federal Open Market Committee

Abstract: The consensual aspects of decision making are essential for understanding policy made by administrative organizations that take the form of a commision or board. Consensual decision making reflects the degree of policy cohesion exhibited by high-level officials within administrative organizations. It is proposed here that this type of behavior may differ between heterogeneous agents. The Federal Open Market Committee (FOMC) of the Federal Reserve System serves as a salient setting for testing these proposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Spencer (2006) adopts a similar econometric approach to the current paper using an ordered probit model to estimate the reaction functions of MPC members. Similarly, Brooks et al (2007) explain MPC voting using an inflated ordered probit (IOP) model comprising a two-equation system of a "long-run" equation capturing a binary decision to change or not change the interest-rate, and a "short-run" one based Krause 1996). Hallmarking many of these studies is a role for political influence through the FOMC appointments procedure and a prominent role for career backgrounds.…”
Section: Relationship To the Literaturementioning
confidence: 99%
“…Spencer (2006) adopts a similar econometric approach to the current paper using an ordered probit model to estimate the reaction functions of MPC members. Similarly, Brooks et al (2007) explain MPC voting using an inflated ordered probit (IOP) model comprising a two-equation system of a "long-run" equation capturing a binary decision to change or not change the interest-rate, and a "short-run" one based Krause 1996). Hallmarking many of these studies is a role for political influence through the FOMC appointments procedure and a prominent role for career backgrounds.…”
Section: Relationship To the Literaturementioning
confidence: 99%
“…If the appointing (contractual) principal is an elected official, bureaucratic agents face greater pressures to be politically responsive (Wilson 1989, 197–200). Elected officials possessing formal appointment powers are more capable of shaping agency behavior than those who do not directly select agency executives (Krause 1994, 1996). Organizational pathologies arising from politicized personnel selection mechanisms range from lower human capital, higher personnel turnover, decreasing morale, and greater difficulty with recruitment and retention of high‐capacity bureaucrats.…”
Section: Organizational Balancing Between Politicization and Autonomymentioning
confidence: 99%
“…This is an important question to pose since the procedural mechanisms used to select agency officials can affect bureaucratic policy decision making. For instance, Krause (1994, 1996) has shown that different appointment mechanisms used to select Federal Open Market Committee members can explain variations in consensual decision making regarding U.S. monetary policy.…”
mentioning
confidence: 99%
“…In order to analyze these scenarios, we have to consider an indicator for future monetary policy preferences.16 This aggregate refers to the area of the EU between2000 and 2006. 17 This has been shown, for instance, for the countries of the EMU in 1990-1998 byGerlach and Schnabel (2000) Krause (1996). bases his model of US monetary policy on the assumption that the countries' representatives consider national inflation and output objectives.…”
mentioning
confidence: 97%